Academic Libraries’ External Environment and Environmental Scanning by Managers - Babalhavaeji, Fahimeh; Farhadpoor, Mohammad Reza (Information World, 2011)
“Importance, variability and complexity” are more common characteristics of organizations’ external environment. Managers scan the external environment in order to acquire information about events and incline to plan the organization’s future courses of action. This study aims first, to investigates the manner that library and information center managers of Islamic Azad University (IAU) perceived the “Importance, Variability and Complexity” of the environmental sectors; and secondly, it aims to calculate the “Perceived Strategic Uncertainty (PSU)” and the “Perceived Environmental Uncertainty (PEU)”, and to account their correlation with the amount of scanning in each environmental sector. Populations of this survey are library and information center managers of large and very large units of IAU, consisting of 94 units of 232 in total. Data are collected by questionnaires by mail and face to face interviews. Results indicate that the amount of scanning is related to the perceived strategic uncertainty (range from 0.339 to 0.745) and perceived environmental uncertainty (range from 0.607 to 0.770); that is PSU and PEU of each environment sector strongly correlates with the amount of scanning. In the field of library and information centers acting as service base organizations, managers who scan the environment, customers, and technologic sectors are perceived as important, variable and complex. The great mean value of competition (mean = 3.88) in the field of complexity shows the complexity of this sector and numerous factors in the field of information services.